2020
DOI: 10.9734/mrji/2020/v30i730239
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Chicken Eggs from Poultry Farms and Retail Markets in the New Juaben Municipality, Ghana

Abstract: This cross-sectional study seeks to investigate the bacterial contamination of poultry products (eggs) produced from selected farms and sold within the major markets in the New Juaben Municipality in the Eastern region of Ghana. A total of 100 eggs were sampled randomly from October to December, 2018 from five poultry farms and five retail markets in the municipality for microbial evaluation. The collected swabs of eggshells and its contents collected at various times of the day were cultured on suitable media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Similar to our findings, a study by Bisong et al (2016) reported that most of the participants in the study stated that legalizing abortion would promote promiscuity (24). In contrast, a study in Ghana that investigated the perceptions of schoolgirls regarding abortion found that most of the respondents disagreed that access to abortion services would result in women having more sexual partners (25). While these two studies did not conduct statistical analysis to assess the correlation between abortion legalization and sexual behavior, a study in the US found evidence to suggest a causal relationship between abortion legalization and increased risky sexual behavior, as well as increased incidences of sexually transmitted diseases (26).…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 84%
See 1 more Smart Citation
“…Similar to our findings, a study by Bisong et al (2016) reported that most of the participants in the study stated that legalizing abortion would promote promiscuity (24). In contrast, a study in Ghana that investigated the perceptions of schoolgirls regarding abortion found that most of the respondents disagreed that access to abortion services would result in women having more sexual partners (25). While these two studies did not conduct statistical analysis to assess the correlation between abortion legalization and sexual behavior, a study in the US found evidence to suggest a causal relationship between abortion legalization and increased risky sexual behavior, as well as increased incidences of sexually transmitted diseases (26).…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 84%
“…Societal norms and economic and legal obstacles have a significant influence on women's decisions to terminate pregnancy (29). On the permissibility of abortion in schoolgirls, several studies have demonstrated that the desire to continue education was among the most popular reasons for girls to opt for an abortion (25,30).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%